VALIDITAS MEDIA PEMBELAJARAN LECTORA INSPIRE BERBASIS DISCOVERY LEARNING PADA MATERI SISTEM REPRODUKSI MANUSIA KELAS XI SMA - syam, sukmawati; Al Anshori, Fitrah; Andriani, Fina (Universitas Cokroaminoto Palopo, 2025)
Lectora Inspire learning media is an interactive learning tool that presents information in the form of text, graphics, and illustrations. This media has many features so it can be used to create more interesting teaching materials. The purpose of this study is to test the validity of the Lectora Inspire learning media based on Discovery Learning on the material of the Human Reproductive System in Grade XI of Senior High School, to ensure its effectiveness in improving student understanding. This type of research uses Research and Development (R&D) with the ADDIE development model. The results of the validity test showed an average value of 97.75% by media experts and validation carried out by material experts obtained an average value of 85%. Based on these results, the Lectora Inspire learning media based on Discovery Learning on the material of the Human Reproductive System in Grade XI of Senior High School is declared valid and suitable for use in learning